Association between motivation to leave the teaching profession profiles and job satisfaction among Omani teachers: A latent profile analysis. (September 2022) - Al'Abri, Khalaf; Alhadabi, Amal; Emam, Mahmoud
Abstract: This study identified distinctive profiles of Omani teachers related to their motivation to leave the teaching (MLT) occupation and estimated differences in teachers' job satisfaction across the estimated profiles. Data on 1625 Omani teachers were analyzed using unconditional and conditional latent profile analysis. The results revealed three latent profiles, including (1) quitters (i.e., teachers with a high level of MLT), (2) moderately engaged teachers (i.e., teachers with a moderate level of MLT), and (3) highly engaged teachers (i.e., teachers with a low level of MLT). Gender and two particular age groups significantly predicted profile membership, allowing for the identification of the characteristics of teachers within each profile.